Fresh aquaculture sludge management with black soldier fly (Hermetia illucens L.) larvae: investigation on bioconversion performances - Giacomo Rossi; Shikha Ojha; Andreas Müller-Belecke; Oliver K. Schlüter (Scientific Reports, 2023)
Abstract Aquaculture solid waste (ASW) is a nutrient rich material that can pose a significant environment challenge if not properly managed. This study investigated the potential of black soldier fly (BSF) larvae in converting this waste into biomass. Five substrates comprising chicken feed supplemented with varying proportions of fresh ASW (0%, 25%, 50%, 75%, 100%) were formulated and evaluated for larval growth and waste bioconversion efficiency. High nutrients retention (N: 23.25 ± 1.40%; C: 21.94 ± 0.99%; S: 12.20 ± 1.33%) and feed conversion ratio (1.78 ± 0.08) were detected on substrate 100ASW, although the limited feeding rate (114.54 ± 5.38 mg dry substrate/larvae) and the high amount of indigestible fibres (ADF = 15.87 ± 0.24%; ADL = 6.36 ± 0.17%) were translated to low larval growth (final larval average weight: 66.17 ± 1.81 mg). Decreasing ASW content resulted in reduced fibres and ash, increase in non-fibrous carbohydrates and C/N ratio, and improved larval growth and substrate utilization. However, high larval metabolic activity suggested higher nutrients loss to the environment. Substrate 75ASW demonstrated the best performances in terms of larval production (final larval average weight: 176.30 ± 12.12 mg), waste reduction (substrate reduction corrected by percentage of ASW: 26.76 ± 0.86%) and nutrients assimilation (N: 22.14 ± 1.14%; C: 15.29 ± 0.82%; S: 15.40 ± 0.99%). This substrate closely aligned with optimal BSF rearing substrates reported in literature. Overall, this study highlights the potential of BSF larvae in managing fresh ASW, offering a dual benefit of waste reduction and insect biomass production.